Profile of isokinetic rotator cuff muscle performance in adolescent state-level weightlifters - Abdul Rahim, Mohamad Faiz (J Taibah Univ Med Sci, 2018)
OBJECTIVES: This study aimed to determine isokinetic profiles of rotator cuff muscle strength and power in adolescent state-level weightlifters. METHODS: Nineteen young state-level weightlifters performed concentric strength tests of the upper limbs using an isokinetic dynamometer. Peak torque/body weight was measured for each weightlifter in dominant and non-dominant limbs. RESULTS: Peak torque/body weight was significantly different in external rotation (p < 0.05); however, there was no significant difference in internal rotation between the limbs. No significant difference was found in time to peak torque between the dominant and non-dominant limbs (p > 0.05). Time to peak torque in external rotation was less in the dominant than in the non-dominant limb. However, opposite results were obtained in external rotation, whereby time to peak torque was longer in the dominant limb compared to the non-dominant limb. Similarly, no significant difference was found between dominant and non-dominant limbs in terms of average power (p > 0.05). CONCLUSIONS: The findings of this study may help in establishing potential imbalance in variables of muscular contractions between dominant and non-dominant limbs of weightlifters. This may help to maximise performance and minimise potential shoulder injury.